PEMETAAN EPIDEMIOLOGI SEBARAN PENDERITA DEMAM BERDARAH DENGUE DI KECAMATAN KOTA BARU KOTA JAMBI TAHUN 2015 - Vera Oktaviani; Susy Ariyani; Krisdiyanta Krisdiyanta (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2016)
Dengue fever (DBD) disease is a contagioused disease caused by dengue virus that is spreadedby Aedes aegypty mosquitos bitting. This disease can attack all people mainly children, even it can causeextraordinary incidents. To overcome it, the innovation way by taking advantange of GeographicInformation System (SIG) to get the spreading sufferers view of DBD based on places, people and time.The purpose of this research is to know epidemiology dividing and DBD sufferers spreading. The space ofthe research is cut to epidemiology dividing, sufferers spreading of DBD of every region based on places,ages, rain capality, and the free flick numbers (ABJ).The kind of this research is descriptive survey in the purpose to see distribution design view,frequency, and determinance of DBD disease by way of dividing at Kota Baru Region Jambi City.The result is that the spreading map of DBD sufferer based on places, ages, and the number offree flick (ABJ) even rain fall at Jambi City and the DBD at Kota Baru Region Jambi City in the year of2015 based on univariat analisys and overlay analisys.The conclusion of epidemiology research, the spreading of DBD based on places characteristicand it most happened at Mayang Mangurai region and Sipin three corner. The suggestions to theCleanliness Department, the early anticipation is needed to the regions with most cases are MayangMangurai region and III sipin corner with the high rain fall from July-December by increasing the destroyingmosquitos nest activities (PSN) of DBD.